Transformation of the Institution of Administrative Complaints in Civilian Uniforms - Bessonova, Olga (Journal of Economic Sociology, 2021)
On the basis of the integration of A. Hirschman’s “voice-exit” theory and the author’s theory of the distribution economy, the universal nature of the institution of complaints as a mechanism for generating new social practices is substantiated, and an analysis of civil complaints is carried out. In restricted access orders, complaints are an attribute of administrative management, while in open access orders, the civil complaints employed are not only received by the authorities but are also presented in public forms. In contrast to the widespread understanding of complaints as a socio-psychological phenomenon, this article reveals the mechanism of their active influence on the formation of the institutional environment throughout its historical development, which explains the revival of this institution as a feedback signal in new digital and communicative forms in the modern Russian economy. To solve this task, we used a methodology of analyzing institutional changes as “a path dependent on the previous development,” which traces the formation and development of the basic institution of complaints at three stages of the evolution of the distribution economy in Russia, as well as the institution’s acquisition of a modern state on the basis of new platforms and authorized public events. As a result, there has been a gradual transition to civil forms of complaints, which include different types of public activity to present unresolved problems. It is established that local protests on socio-economic issues, in fact, are an unformalized part of the institution of complaints and actively influence decision-making in the modern management model.